New developments in the understanding of the pathophysiology of muscle pain - Mense, Siegfried; Hoheisel, Ulrich (Journal of musculoskeletal pain, 1999)
Objectives: The review gives an overview of recent data on spinal mechanisms of muscle pain obtained in animal experiments. Possible parallels between these data and symptoms in patients with muscle pain are discussed.Findings: The afferent input from inflamed muscle activates neuroki-nin-1 [NK-1] and N-methyl-D-aspartate [NMDA] receptors in the spinal cord, which leads to hyperexcitability of dorsal horn neurons. Simultaneously, the background activity in some spinal segments rose. During longer-lasting lesions, the excitability and background activity of the neurons changed independently from each other. After 12 d of a myositis the excitability of the neurons began to return to normal values, whereas the background discharge continued to increase. The substance P [SP] content of the dorsal horn remains approximately constant during acute and subacute myositis, i.e., the decrease of neuronal excitability during persistent myositis occurs in spite of an unchanged SP content.In the reported studies, nitric oxide [NO] was found to be not involved in the control of excitability of dorsal horn neurons. However, NO had a strong action on the background activity of the cells. The spinal neurons that synthesize NO react in a sensitive and differential way to muscle lesions. Following a lesion the number of the NO cells first increases and then decreases with a time-course that depends on the frequency of the C-fiber input and hence on the severity of the lesion.Conclusions: Afferent input from a damaged muscle is very effective in inducing neuroplastic changes [hyperexcitability and increase in background activity] in sensory neurons of the spinal cord. The hyper-excitability is assumed to cause hyperalgesia in patients; the background activity, spontaneous pain. The data suggest that during sub-acute myositis the hyperalgesia decreases, whereas spontaneous pain increases more and more. The enzymatic activity of NO synthesizing neurons is strongly influenced by a muscle lesion. As NO is one of the main factors that controls the background activity of nociceptive spinal neurons, these cells are likely to determine the degree of spontaneous pain in an awake individual.